Potassium Behavior with Clay Minerals Composition under Soil Ecosystem: it’s Adequacy for Maize Plants - Abou Kota, Mohamed El Sayed; Darwish, Hany Abdelaty; Abdel Aziz, Mohamed Ahmed (American Journal of Agriculture, 2022)
Purpose: The target area for the study is one of the agricultural areas of importance in Egypt. It is a suitable area for studying the origin and distribution patterns of clay minerals. Therefore, the focal aims of this study were: (1) to examine the clay minerals' origins in semi-arid regions of Egypt. (2) The behavioral pattern of K in clay minerals in ecological changes, (3) the reflection of K-behavior in soil on the maize plant's nutrient content under soil systems. Methodology: Evaluation of water samples were: Evaluate the pH and EC, soluble ions, sodium adsorption ratio (SAR), soluble sodium percentage (SSP), sodium to calcium activity ratio (SCAR), residual sodium bicarbonate (RSBC), and residual sodium carbonate (RSC). Also, Evaluation of soil samples were: Evaluate the particle size distribution, OM content, soil pH, Gypsum, CaCO3 content, cation exchange capacity (CEC), exchangeable sodium percentage (ESP), EC, soluble ions, Soil available K, exchangeable K, and total K. Separation of the clay fraction: preparation of soil samples for mineralogical analysis. Qualitative clay mineralogical analysis: X- ray diffactograms were obtained for some selected clay samples using Philips equipment pw (1140/90). Evaluation of plant samples were: Evaluate the N, P, and K concentrations. Statistical analysis: SPSS (v. 20) was used to determine the descriptive statistics and correlation analysis. Findings: Achieving study aims, a series of methodological steps were implemented to study soil and water properties, and their reflection on maize plants. The irrigation water results analysis showed no problems. The soil properties were also distinguished by the results: common features of this type of soil are a depth of greater than 120 cm, a slightly well-drained clay texture, and poor OM content. The CaCO3 content increases with depth. The available N, P, K were (slight to moderate, very low, and good) respectively. The EC values range from non-saline to moderate saline. As indicated, the X-ray diffraction patterns of the clay fractures are separated from those features. It appears from the analysis that the mineral composition of the clay fracture at both areas is dominated by montmorillonite, kaolinite, and then hydrated mica. Based on the studied soil characteristics, there was a reflection on the maize plant grown, which showed the following: A strong positive correlation between the soluble K content and K in maize plants at the age of 30 days. The multiple correlations were significantly positive between the N and P content available to the grain of maize plants. The results exposed a negative correlation between the available K and K content of maize plants at 45 days of age. Also, there was a significant negative correlation between the exchangeable K and K content in maize plants at 60 days of age. Contribution to theory, practice and policy: The results presented the significant relationships between the evaluation of the physical and chemical properties of the soil, the content of available nutrients, as well as the type of soil minerals, and their reflections and contributions on the elements contained in the different parts of the maize plants (stems and grains), according to the state of the maize plants age.